Map Use Competence. Theoretical Basis and the Design of a Competence Model - Hemmer, Ingrid; Hemmer, Michael; Hüttermann, Armin; Ullrich, Mark (Journal of Geography Education, 2010)
This article aims at designing a theoretically based structural model of map use competence. In addition to the geographical concept of maps the model of reading competence of PISA and other concepts are discussed. In chapter 3 the main results of empirical studies to map use competence are discussed, and chapter 4 displays the competence model as the present result of discussion by the authors. On this basis an empirical study is planned, which is outlined in chapter 5.